2019
DOI: 10.1002/jso.25708
|View full text |Cite
|
Sign up to set email alerts
|

Treatment outcome of chest wall soft tissue sarcomas: Analysis of prognostic factors

Abstract: Background: Primary soft tissue sarcomas (STSs) involving the chest wall are uncommon. The aim of this study was to identify factors that influence the prognosis of patients with primary chest wall STS. Methods: The records of 38 patients (23 men and 15 women) who were treated at our institutions during 2002 to 2018 were reviewed. The following variables were evaluated as potential prognostic factors: sex, tumor size, chemotherapy, and completeness of surgical margins. Multivariate analysis was conducted to id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…The underlying mechanism may be the resistant selection and disseminating cancer stem cells induced by chemotherapy at the site of the primary tumour, chemotherapy-induced recruitment of immune cells conducive to the dissemination of primary tumour cells, and mobilization/regulation of circulating tumour cell heterogeneity [ 42 , 43 , 44 , 45 ]. In terms of STS, in a recent study, researchers found that adjuvant chemotherapy was a poor prognostic factor for disease-free survival in chest wall STS patients (HR: 2.797; 95% CI: 1.057–3.409; p = 0.04), which was consistent with our results [ 46 ]. Meta-analyses also cannot prove the advantage of cytotoxic treatment in STS.…”
Section: Discussionsupporting
confidence: 92%
“…The underlying mechanism may be the resistant selection and disseminating cancer stem cells induced by chemotherapy at the site of the primary tumour, chemotherapy-induced recruitment of immune cells conducive to the dissemination of primary tumour cells, and mobilization/regulation of circulating tumour cell heterogeneity [ 42 , 43 , 44 , 45 ]. In terms of STS, in a recent study, researchers found that adjuvant chemotherapy was a poor prognostic factor for disease-free survival in chest wall STS patients (HR: 2.797; 95% CI: 1.057–3.409; p = 0.04), which was consistent with our results [ 46 ]. Meta-analyses also cannot prove the advantage of cytotoxic treatment in STS.…”
Section: Discussionsupporting
confidence: 92%
“…However, it is widely accepted that the clear margin and the grade of tumor are the vital factors related to longterm outcomes. [29][30][31] Limitations exist in this study. First, the current retrospective study was from a single center and had a small sample size.…”
Section: Discussionmentioning
confidence: 94%
“…At present, the diversity in histological types of the sternal tumor and the heterogeneity between literature are nonnegligible, there are no specific guidelines for the sternal tumor. However, it is widely accepted that the clear margin and the grade of tumor are the vital factors related to long‐term outcomes 29–31 …”
Section: Discussionmentioning
confidence: 99%
“…Histologic analysis has a variable distribution of subtypes of fibrosarcoma, malignant fibrous histiocytoma, chondrosarcoma, or potentially radiation-induced sarcomas such as angiosarcoma following treatment for breast cancer. 21,22 Soft-tissue coverage of the chest wall can be accomplished using a variety of different modalities. In circumstances where a suitable wound bed is present, a skin graft potentially represents the simplest approach, although this often results in a suboptimal cosmetic result with poor long-term durability, particularly in the setting of prior radiotherapy.…”
Section: Trunk and Chest Wallmentioning
confidence: 99%